Influence of Early Ring Closure of Center Drift on Main Tunnel Excavation Under High Overburden Conditions - NAT2024 - Devini Abeyawardena; Simin Zhai; Sadatoshi Ohmori (Society for Mining, Metallurgy & Exploration, 2024)
A road tunnel is planned to be constructed in soft, high overburden ground of around 600 m in Japan by using the center drift advancing method. The dodging effect and early ring closure of the center drift were expected to reduce the displacement and deformation of tunnel and promote safe construction. The measurement result during construction was analyzed and those effects, which the displacement and deformation after the widening excavation decreased and its effect increased as the center drift radius increased, were confirmed by numerical analysis. Also, the effect of the early closure of center drift after widening excavation did not have much effect.